Tema Konservasi Lingkungan Hidup pada Buku Antologi Cerpen Lingkungan (ANCELI) Karya Ni Putu Anik Erawati dkk: Sebuah Kajian Ekokritik - Khanifah, Rokhmatul; Israhayu, Eko Sri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to describe the form of ecocriticism that reflects environmental ethics and environmental conservation efforts in the book Antologi Cerpen Lingkungan (ANCELI) by Ni Putu Anik Erawati et al. This type of research is qualitative research with an ecocriticism approach to environmental ethics literature. The data analysis method in this study is to categorize the forms of ecocriticism that reflect environmental ethics, then indicators are created for each category so that in the discussion they will be discussed according to the indicators, after which each data is connected to environmental conservation efforts. The data in this study are data contained in short stories in the form of words, sentences, expressions, and narrative stories that contain forms of ecocriticism of environmental ethics and environmental conservation efforts. The data source in this study is the book Antologi Cerpen Lingkungan (ANCELI) by Ni Putu Anik Erawati et al. first published in 2024. The data collection techniques used in this study are reading techniques and note-taking techniques. The data analysis techniques used in this study are data reduction, data presentation, ad drawing conclusions. The results of the study showed that there were nineteen forms of ecocriticism that reflected environmental ethics and conservation efforts. First, there are two attitudes of respect for nature. Second, there are nine data on respectful attitudes towards nature. Third, there is a principle of solidarity. Fourth, there are four principles of love and concern for nature. Fifth, there are two principles of not harming nature. Sixth, there is a principle of living simply and in harmony with nature